Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Limited role of continental arc in crustal growth: Insights from zircon U-Pb ages and Lu-Hf isotopes of late Paleozoic granitoid plutons from the northern North China Craton - Jing Ran; Hao Wang; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Yu-Sheng Zhu (Lithos, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Macro–mesoscopic damage evolution and constitutive modeling of bio-reinforced weak interlayer zones under cyclic excavation disturbance - Shu-Qian Duan; Jing-Ran Wang; Xi-Qing Jiang; Jie-Cheng Xiong; Shi-Hao Liu; Ding-Ping Xu; Yun-Long Liu; Jing-Wei Zhang; Wei Liu; Chun-Yu He (Bulletin of Engineering Geology and the Environment, 2026)

Comparative analysis on antioxidant capacity, immunity and mortality changes of pikeperch (Sander lucioperca) in response to mono-infection or co-infection with Nocardia seriolae and Aeromonas salmonicida - Junchen Li; Jing Wang; Zhipeng Sun; Ran Zhao; Xianhu Zheng; Shaowu Li; Cuiyun Lu; Di Wang (Aquaculture, 2026)

Efficient stabilization and mechanism of graphite nanoplatelets for water-in-oil emulsions - Qiuyue Wang; Jie Sun; Yu Feng; Ran Yin; Hongyin Kang; Jiaqiang Jing (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of lipid degradation and the Maillard reaction: Decoding the flavor formation of charcoal-grilled lamb skewers based on flavoromics, sensomics, metabolomics, and lipidomics - Che Shen; Xinyu Jiang; Jiajin Sun; Meiyi Li; Ran Wang; Yunhui Zhang; Jing Tian; Lizhang Wu; Xiongfeng He; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

A validated field-to-model framework for pesticide residue prediction and dietary risk assessment in pear production - Ran Yi; Chen Chen; Nan Huang; Xinquan Wang; Yanhua Wang; Jing Wang (Food Control, 2026)

Terrestrial expression of the Jenkyns Event: Integrated records from the Eastern Tethys, China - Xiaowei Liu; Ran Gao; Kai Zhou; Shuo Zhang; Jing Lu; Rongtao Guo; Zhiming Yan; Peixin Zhang; Xiaotao Xu; Wanqing Wang; Minfang Yang; Longyi Shao; et al. (Earth-Science Reviews, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Carboxymethyl cellulose-metal organic frameworks composites: From synthesis to applications - Hongyu Wang; Ran Song; Guiru Chen; Fei Wang; Luying Wang; Jing Liu; Jiandu Lei (Carbohydrate Polymers, 2026)

CNF-stabilized liquid metal reinforced dual-network anti-freezing hydrogel for multifunctional wearable bioelectronics - Hongyu Wang; Guiru Chen; Ran Song; Fei Wang; Luying Wang; Jing Liu; Jiandu Lei (Chemical Engineering Journal, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Lower-molecular-weight yeast mannan polysaccharides beneficially modulate gut microbiota and fermentation profiles in broilers: An in vitro and in vivo assessment - Junwei Bao; Luqian Gong; Yuhua Zhao; Ran Wang; Jing Bai; Jinlong Liu (Biocatalysis and Agricultural Biotechnology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

A long-term high-resolution national assessment of N2O emissions from Chinese lakes and reservoirs - Jing Wei; Huixiao Pan; Yunjie Zhang; Wenping Yuan; Hongtao Duan; Lishan Ran; Xiuzhi Chen; Faming Wang; Zhangcai Qin; Shilong Piao (Science China Earth Sciences, 2026)

Machine learning-informed uncertainty analysis in life cycle assessment of alternative marine fuels - Run Liu; Jing Wang; Ran Yan (Transportation Research Part D: Transport and Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Reductive degradation of bromate in drinking water by far-UVC photolysis of sulfite - Zhengyang Wang; Xi Zhang; Yimeng Ma; Ran Yin; Jing Zhao (Journal of Hazardous Materials, 2026)

Radio frequency-enhanced remediation of PAHs-contaminated soils using peroxydisulfate: Performance and mechanistic insights - Wenhao Qi; Anxu Sheng; Dawei Lan; Zezhou Zhao; Yao Shi; Fengjiao Zhang; Jiang Lin; Ying Ran; Wei Lou; Jing Chen; Xiaohui Wu; Linling Wang (Journal of Environmental Management, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Reservoir inflow forecasting using a large language model and time series approach - Zixin Song; Ping-an Zhong; Yiwen Wang; Yu Han; Bin Wang; Xinyuan Qian; Ran Mo; Weifeng Liu; Jing Liu (Environmental Modelling & Software, 2026)

Carbon cycle perturbations during the late Devonian Upper Kellwasser event and their role in the biotic crisis - Kai Zhou; Ran Gao; Haoqing Liu; Jing Lu; Rongtao Guo; Peixin Zhang; Wanqing Wang; Zhiming Yan; Xiaowei Liu; Na Qian; Longyi Shao; Shuo Zhang (Earth-Science Reviews, 2026)

A biomass-derived modular hydrogel platform for multimodal physical, chemical, and biological sensing - Hongyu Wang; Guiru Chen; Ran Song; Fei Wang; Luying Wang; Jing Liu; Jiandu Lei (Chemical Engineering Journal, 2026)

Physical and biological synergistic strategies: injectable CNF/CMC hydrogels with cannabidiol@PCL microspheres for durable facial filling - Hongyu Wang; Guiru Chen; Ran Song; Fei Wang; Yunjian Chen; Luying Wang; Jiandu Lei; Jing Liu (Carbohydrate Polymers, 2026)

A novel low-resistance cylindrical annular vent plenum chamber with uniform outflow designed via three-dimensional flow topology optimization - Zijing Fan; Ruoyin Jing; Ran Gao; Ao Tian; Junkai Ren; Dongzheng Wang (Building and Environment, 2026)

Development of a rapid and visual detection platform for Aeromonas salmonicida based on the RPA-CRISPR/Cas12a system - Fusheng Tan; Ran Zhao; Jing Wang; Di Wang; Shaowu Li (Aquaculture, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Recurrent Middle Jurassic (Aalenian) wildfires in the Qaidam Basin, NW China: Palaeoclimatic controls and carbon cycle implications - Kai Zhou; Rongtao Guo; Shuo Zhang; Xiaowei Liu; Jing Lu; Ran Gao; Peixin Zhang; Zhimin Yan; Haoqing Liu; Weichao Wang; Longyi Shao (Global and Planetary Change, 2026)

Phage tail Fiber-based electrochemical biosensor for rapid detection of Cronobacter spp. in food - Hao Hu; Xiangmu Yang; Shaowen Guo; Jing Wang; Tao He; Ran Wang; Lili Zhang; Heye Wang (Food Research International, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

A simple method to estimate seismic subsidence in soft soil under amplitude non-stationary seismic action - Gan-Ling Xian; Jing-Yan Lan; Li-Chun Chen; Yong-Zhi Wang; Lei Wang; Zhao-Ran Wu (Engineering Geology, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Multiple magmatic episodes and metamorphic overprinting in the Archean Anshan Complex: Integrated zircon–rutile–titanite–apatite U–Pb geochronology and trace-element constraints - Qing-Feng Mei; Jin-Hui Yang; Jin-Feng Sun; Lei Xu; Jing Ran; Bao-Quan Zhou; Ya-Dong Wu; Hao Wang (Lithos, 2026)

Environmental VOC exposure and mental health - Jianhui Guo; Feifei Si; Ran Huang; Xinlu Wang; Yuqi Shi; Guiying You; Yaqi Wang; Di Shi; Xinyao Lian; Shuyue Li; Junyu Lu; Shaodong Xie; et al. (Journal of Hazardous Materials, 2026)

Completing the puzzle of aged microplastics towards microalgae at environmental concentration: effects of polymer type, size, aging method, and aging duration - Ming-Zhi Shen; Liu Yang; Yi-Ran Zhai; Jing-Han Wang; Zhan-You Chi; Qiang Zhang (Journal of Cleaner Production, 2026)

Digestible properties and formation mechanism of rice starch-gelatin-tea polyphenols ternary composite gel: Effect of tea polyphenol concentration, type of gelatin and gelatin/starch ratios - Chen-Chen Wang; Jing-jing Xu; Yan Liu; Fan Wang; Ran Feng; Bao Zhang (Food Hydrocolloids, 2026)

Enhancement of microalgal biofilm growth and atmospheric CO2 capture by metal-organic frameworks (MOFs): Influences of MOF type, dosage, and calcination conditions - Tong Wu; Yi-Ran Zhai; Jing-Han Wang; Zhan-You Chi; Jian-Gang Ren (Chemical Engineering Journal, 2026)

Linking dissolved organic matter sources to greenhouse gas potential in thermokarst lakes of the Qinghai–Tibet Plateau - Wenyan Liu; Zeyong Gao; Chengming Zhang; Fujun Niu; Yibo Wang; Zhanju Lin; Youhua Ran; Jing Luo; Guoan Yin; Yunhu Shang (Cold Regions Science and Technology, 2026)

Can we have our cake and eat it too? A collaborative pathway for ecological conservation and high-quality development in the river-sea convergence zone of the Yellow River Basin - Ran Shang; Meixian Wang; Wen Wang; Qingqing Zhang; Jing Li (Frontiers in Marine Science, 2026)
In river-sea confluence zones, where land-sea interactions are highly concentrated, achieving synergy between ecological conservation and high-quality development is essential for regional sustainability. As the only river-sea transition zone in the Yellow River Basin, Shandong Province serves as a critical ecological security barrier while facing increasing pressure from intensive development and resource-environment constraints. Against this backdrop, this study takes Shandong Province as the research area and constructs a multi-level analytical framework integrating ecological conservation and high-quality development. From the dual perspectives of intra-system coordination and inter-system coupling, it evaluates coordination levels and identifies spatial differentiation patterns under land-sea integration. The results show that ecological conservation in Shandong is generally coordinated, forming “acore-periphery” spatial pattern, although uncoordinated areas remain concentrated along major rivers and lake regions. High-quality development remains at a relatively low level overall, with pronounced imbalance among the five development concept subsystems; in particular, innovation exhibits weak coordination with other subsystems and constitutes a key constraint. Moreover, the relationship between ecological conservation and high-quality development is dominated by incoordination, with more than 70% of the area classified as uncoordinated, while coordinated regions are mainly distributed in southern Shandong and parts of the Jiaodong Peninsula, showing a fragmented pattern. These findings indicate that the coordination relationship is jointly shaped by resource-environment constraints and land-sea coupling processes. By incorporating a land-sea integrated perspective, this study refines the analytical framework for understanding the interaction between ecological conservation and development, and provides empirical support for differentiated governance and sustainable development in river-sea transitional zones.

Airborne and fecal resistome restructuring after antibiotic growth promoter ban in the livestock farms - Ran Cao; Lu Song; Can Wang; Yuan Zhang; Jing Wang (Journal of Environmental Sciences, 2026)

Compartment-specific assembly and functional characterization of the bacterial microbiome in a Pinus radiata- Lactarius deliciosus plantation system - Jing Yuan; Yanliang Wang; Xueqiong Zhang; Zhuyue Yan; Ran Wang; Chengmo Yang; Xinhua He; Jesús Pérez-Moreno; Fuqiang Yu; Yi Zheng (Applied Soil Ecology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Construction of Kongyu 131 mutant library provides genetic resources for rice functional genomics and germplasm improvement - Tingting Xu; Qun Yang; Ran Li; Jianping Wang; Zhishan Luo; Daoyong Gong; Leihao Weng; Xiaoshan Huang; Debao Fu; Jing Li (Plant Science, 2026)

Embryonic Proto-Tethys Ocean: Evidence from the early Ediacaran Kuyake ophiolite mélange along the Altyn Tagh in NW China - Hong-Ran Wang; Chuan-Lin Zhang; Hua-Dong Ma; Yan Jing; Masumeh Sargazi; Zhi-Hao Song (Precambrian Research, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Differential robustness of microalgal-bacterial biofilm to once and consecutively changing multi-stressors: Combined impacts of salinity, nutrients, and hydrodynamic loads - Yang Liu; Yi-Ran Zhai; Xiang-Yi Kong; Jing-Han Wang; Zhan-You Chi; Jian-Gang Ren (Bioresource Technology, 2026)

Transcriptomic and Physiological Insights into GA₃-Mediated Regulation of Fruit Abscission in Lonicera Caerulea L - Kailin Shao; Jing Chen; Bingbing Ren; Dong Qin; Xueting Wang; Chunlin Fu; Ran Gu; Jiacheng Li; Zhonglin Jia; Zhenyu Li; Junwei Huo; Huixin Gang (Journal of Plant Growth Regulation, 2026)

miR-199-3p protects chicken granulosa cells from ferroptosis by targeting ZEB1 and activating Wnt/β-catenin signaling - Jinshan Ran; Wei Huang; Yanli Du; Xiao Wang; Tiao Ning; Jing Li (Theriogenology, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Bioinspired lignin-based coatings for durable and photothermal antibacterial surfaces - Cheng Wang; Bowen Ran; Kexin Li; Xiaodong He; Jing Li; Yunjie Xiang; Kun Xu; Xi Rao; Selvakumar Murugesan; Valentim A.R. Barão; En-Tang Kang; Liqun Xu (Chemical Engineering Journal, 2026)

Carboxymethyl cellulose hydrogels for flexible electronics: From design to applications - Hongyu Wang; Ran Song; Guiru Chen; Fei Wang; Luying Wang; Jiandu Lei; Jing Liu (Carbohydrate Polymers, 2026)

Continuous adjoint optimization method for building fluid systems based on mesh-adaptive deformation with a low deformation rate relaxation mechanism - Yingying Wang; Ruoyin Jing; Nan Li; Ran Gao; Ao Tian; Junkai Ren; Yibu Gao; Shu He (Building and Environment, 2026)

Analysis of the resistance and flow characteristics of a square diffuser under adjacent influence conditions based on design of experiments - Haimeng Li; Wei Xu; Ran Gao; Xinyu Zhang; Chi Zhang; Yan Tian; Yi Wang; Ruoyin Jing (Building and Environment, 2026)

Biomass-based dual-network multifunctional hydrogel for durable wearable sensors and emergency hemostasis - Hongyu Wang; Ran Song; Guiru Chen; Fei Wang; Luying Wang; Jiandu Lei; Jing Liu (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Phage-cocktail-based biocontrol of multidrug-resistant Klebsiella pneumoniae both in vitro and in vivo - Ling Zou; Yang Yu; Dongxue Yue; Chuanxu Wang; Shijie Xu; Wenhua Liu; Shouzhen Xu; Jing Ma; Hong-Bo Ni; Tao He; Ran Wang; Yehui Sun; et al. (Archives of Virology, 2026)

Effects of chronic social defeat stress on behavior and cognition by activating the ERS-NLRP3 signaling pathway in adult mice - XiaoLei Gao; Ran Hao; ZengYun Jing; GuangBiao Huang; Lina Wang; Anna Ma; ZhaoHui Zhang; Tong Zhao (Metabolic Brain Disease, 2025)

Sedimentological and geochemical evidence of Early Permian coal accumulation patterns linked to paleoclimate: Example from the Liujiang Basin, North China - Kai Zhou; Minfang Yang; Shuo Zhang; Ran Gao; Zhiming Yan; Peixin Zhang; Lei Wang; Haoqing Liu; Xiaowei Liu; Longyi Shao; Jing Lu (Marine and Petroleum Geology, 2025)

An explainable ensemble deep learning model for long-term streamflow forecasting under multiple uncertainties - Xinyuan Qian; Bin Wang; Juan Chen; Yukun Fan; Ran Mo; Chengjing Xu; Weifeng Liu; Jing Liu; Ping-an Zhong (Journal of Hydrology, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Influence of organic acids on phosphorus recovery via vivianite crystallization: New insights based on spectroscopic analysis and DFT calculations - Su-Na Wang; Ran Ge; Jia-Shun Cao; Jing-Yang Luo; Fang Fang (Journal of Environmental Chemical Engineering, 2025)

Impact of κ-carrageenan and locust bean gum on physicochemical properties and emulsion gel formation in casein-based systems - Zhengji Lu; Zhixian Wu; Kehan Wu; Xiaoying Zhang; Ying Zhang; Jing Zhang; Hui Zhou; Xiankang Fan; Lei Zhou; Ran Wang; Jie Luo (Food Hydrocolloids, 2025)

Synergistic effects of co-infection with Flavobacterium psychrophilum and Aeromonas salmonicida on mortality, pathophysiology, and immune responses in rainbow trout (Oncorhynchus mykiss) - Jing Wang; Ran Zhao; Yanan Wang; Bingchen Guo; Shaowu Li; Di Wang (Fish & Shellfish Immunology, 2025)

Genome-Wide Identification and Characterization of the Trihelix Transcription Factor Family in Polygonatum kingianum and Gene Expression Pattern Analysis Under MeJA Treatment - Chun-Yu Chen; Wan-Bo Ding; Hong-Jing Zhang; Yan-Ran Qi; Wen-Xiang Wang (Plant Molecular Biology Reporter, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

A low-resistance reducer optimization method and manufacturing process based on Bézier curves and machine learning - Ao Tian; Ruoyin Jing; Junkai Ren; Yingying Wang; Yibu Gao; Yi Wang; Yan Tian; Lei Shi; Zhong Yu; Shengrui Yu; Ran Gao (Building and Environment, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Comparative DFT study on the reaction mechanism of dry reforming of methane over Ni (111), Ni@Co (111) and Co (111) surface - Zhiliang Ou; Qingsong Zuo; Ziqiang He; Kai Wang; Wenpin Zhang; Xiuquan Li; Jing Liang; Ying Chen; Jingyu Ran (Fuel, 2025)

Elucidation of the thermal aggregation processing of soy protein isolate – dialdehyde carboxymethyl cellulose cross-linked gel - Yidan Fu; Ran Tian; Jiarui Zhao; Jing Wang; Xiaonan Sui (Food Chemistry, 2025)

Elucidating the mechanism of dibutyl phthalate on Alzheimer's disease through network toxicology, molecular docking and validation in mouse neuroblastoma cells - Jing Zi; Xinlong Li; Qianqian Cao; Yifan Hu; Zhichang Ran; Yanliu Li; Jiayuan He; Xiaoyu Wang; Guo Cheng; Jingyuan Xiong (Food and Chemical Toxicology, 2025)

Synergistic effect of dual vacancies and interface structure enables 100 % CH4 selectivity for CO2 photoreduction - Jing Tian; Wenjuan Li; Weiguang Ran; Yuhua Wang; Kuanchang Liu; Na Li; Tingjiang Yan (Chemical Engineering Journal, 2025)

Study on the resistance calculation method for ventilation duct systems under non-fully developed flow conditions - Yi Wang; Sen Yang; Ran Gao; Yan Tian; Ruoyin Jing; Angui Li (Building and Environment, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Mannan oligosaccharides reduce the carbon footprint by decreasing methane emission and nitrogen excretion in Xiangdong black goats - Jing Wang; Ting Liu; Jianfeng Xu; Huihui Liu; Kang Sun; Huiyu Fan; Shengxin Zhu; Hang Ran; Chen Zheng (Animal Feed Science and Technology, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Short-term nutrient addition increases soil organic carbon accumulation in tropical forest - Tianyan Su; Yamin Jiang; Huaying Chen; Ying Wang; Qiu Yang; Jialing Li; Jing-li Lu; Hongyu Ran; Huai Yang; Wenjie Liu; Mengyang Fang; Lianghong Huang (Plant and Soil, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Strip application of organic fertilizer in the root zone increases the substitution ratio of chemical nitrogen and sunflower yield in saline-alkali soil - Ran LI; Shujuan WANG; Jia LIU; Erzhen LI; Junxia MIAO; Xiaoliang WEN; Jing YANG; Lizhen XU; Binrui LI; Cunwang JIN; Yan LI; Yonggan ZHAO (Pedosphere, 2025)

Temporary plugging ball migration behavior of multi-cluster hydraulic fracturing in horizontal wells based on macroscopic particle model - Zhiguo Wang; Wei Jing; Ran Wei; Shuai Li; Yuting Men; Feng Zhang; Li Sun (Fuel, 2025)

Numerical investigation of the hygrothermal and energy performance of passive temperature-humidity regulation walls in various climate zones - Dongxia Wu; Zhaoyuan Shang; Jing Hou; Hailing Fu; Zhili Sun; Huan Sun; Yongan Yang; Tianlei Wang; Ran Chen; Mohammed El Ganaoui (Building and Environment, 2025)

An air balancing method for ventilation systems considering random fluctuations: Flow prediction and operating condition optimization - Yi Wang; Ran Gao; Yan Tian; Ruoyin Jing; Mengchao Liu; Angui Li (Building and Environment, 2025)

Microglial purinergic signaling in Alzheimer’s disease - Shu-Ya Mei; Ning Zhang; Meng-jing Wang; Pei-ran Lv; Qi Liu (Purinergic Signalling, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

An ultra-sensitive, intelligent platform for food safety monitoring: Label-free detection of illegal additives using self-assembled SERS substrates and machine learning - Chunjuan Yang; Shuang Jiang; Yue Zhao; Li Zhang; Xiaoming Lyu; Shulu Zhang; Jiayue Liang; Yiyang He; Xubin Quan; Mingxu Zhang; Ran Gao; Renxing Song; et al. (Food Chemistry, 2025)

Air flow field Testing, simulation and Optimization of CO2 air-source heat pump outdoor unit arrays - Li Xiaoyu; Shi Lin; Ma Li; Xu We; Wang Tiansheng; Zheng Siyu; Tian Ran; Yuan Jing; Cui Yujia (Energy and Buildings, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Volcanism-driven synchronous terrestrial and marine anoxia during the Kungurian (early Permian) - Kai Zhou; Minfang Yang; Shuo Zhang; Ran Gao; Peixin Zhang; Longyi Shao; Weichao Wang; Lei Wang; Jing Lu; Jason Hilton (Gondwana Research, 2025)

Cost-effective, label-free electrochemical aptasensors for rapid detection of concanavalin A with screen printed electrodes - Chenze Lu; Gongyan Wang; Xiaoxiao Zhang; Zhihui Fang; Xinyuan Wang; Fan Tang; Kang Ning; Min Xu; Jing Wang; Han Jiang; Ran Tao; Pei Xu (Food Chemistry, 2025)

Comparison and mechanism analysis of fatty acid differences between backcross F2 derived from blunt snout bream (Megalobrama amblycephala,♀) × topmouth culter (Culter alburnus,♂) and its closely related species - Qixiang Wang; Haoyang Wangchen; Junhan Luo; Yanling Qing; Ran Jiang; Yanan Luo; Xing Gao; Jing Liu; Zhenfeng Chen; Yanfang Li; Shenping Cao; Jianzhou Tang; et al. (Aquaculture International, 2025)

CRISPR-RPA biosensor with digital glucometer-based diagnostics of zoonotic fish-borne clonorchiasis - Xiaoxiao Ma; Jing Ding; Junpeng Song; Bin Tang; Yiming Fang; Ran Wang; Mingyuan Liu; Xiaolei Liu; Chen Li (Food Control, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

Evolution of interfacial electro-chemo-mechanics in high-energy-density NCM811||Si/C-composite Lithium-ion pouch cells - He Ma; Shujun Cai; Ran Song; Kexuan Jing; Min Wu; Weizong Wang; Yurong Ren; Qian Zhao; Zhengping Ding (Chemical Engineering Journal, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Advances in catalysts for the one-step preparation of aromatics by bifunctional catalytic route from syngas - Jiaqi Jiao; Chunquan Liu; Guohui Zhang; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Jing Liu; Jian Ding; Ran Wang; Jingang Yao (Fuel, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Loss of KIFC1 activity induces spindle instability and actin defects during porcine oocyte maturation - Yu-Ran Wang; Peng-Jie Wang; Le-Yan Tao; Lin-Lin Hu; Qiang-Qiang Liu; Shao-Chen Sun; Jing-Xi Wei; Yue Wang (Theriogenology, 2025)

Carboniferous, not Paleoproterozoic, eclogite-facies metamorphism in the northern North China Craton as revealed by in situ garnet Lu-Hf and U-Pb geochronology - Yao-Qi Yan; Hao Wang; Jin-Hui Yang; Shi-Tou Wu; Jing Ran; Bao-Quan Zhou; Ya-Dong Wu (Earth and Planetary Science Letters, 2025)

Inactivation of porcine epidemic diarrhea virus as a SARS-CoV-2 surrogate at sub-zero temperatures by isochoric freezing - Chenang Lyu; Xinyu Liang; Jing Jiang; Fengqing Wang; Ran An; Jielin Yang; Dapeng Wang (Cryobiology, 2025)

Petrogenesis of rodingites along the northern margin of the North China Craton: Constraints from zirconology and whole-rock geochemistry - Jing Ran; Hao Wang; Jinhui Yang; Yaoqi Yan; Yusheng Zhu; Baoquan Zhou (Science China Earth Sciences, 2025)

Role of hepatocyte-specific FOXO1 in hepatic glucolipid metabolic disorders induced by perfluorooctane sulfonate - Jing Yang; Longfei Li; Ziwen An; Yi Lv; Ran Li; Jing Li; Mingmei Guo; Heming Sun; Huiling Yang; Lei Wang; Yi Liu; Huicai Guo (Environmental Pollution, 2025)

A method for demand controlled ventilation based on a pressure loss model under conditions of non-fully developed flow - Yi Wang; Ran Gao; Mengchao Liu; Angui Li; Yan Tian; Ruoyin Jing (Building and Environment, 2025)

Topology optimization of bend for reducing the local resistance in a piping and duct system - Yan Tian; Ran Gao; Ruoyin Jing; Yi Wang; Angui Li; Xin Dong; Xinpeng Hao; Zheng Ji (Building and Environment, 2025)

Apatite geochemical indicators for magma mixing and fractional crystallization in the origin of A-type granite - Bao-Quan Zhou; Jin-Hui Yang; Jin-Feng Sun; Hao Wang; Yu-Sheng Zhu; Ya-Dong Wu; Qing-Feng Mei; Lei Xu; Jing Ran (Lithos, 2025)

Responses of intestinal microbiota to inulin was initial microbiota context dependent and affected by the supplementation dosage - Ran An; Xilong Zhou; Jing Zhang; Chenang Lyu; Dapeng Wang (Food Research International, 2025)

Phosphorus bioavailability and recycling potential in various organic Waste: Assessment by enzymatic hydrolysis and 31P NMR - Xueling Ran; Naga Sai Tejaswi Uppuluri; Yun Deng; Shengrui Wang; Zhaokui Ni; Jing Hu; Joachim Müller; Renjie Dong; Jianbin Guo; Hans Oechsner (Bioresource Technology, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

Harnessing natural light: Novel nanoheterojunction photocatalyst NaGdF4:Yb,Tm@TiO2/Cu2(OH)2CO3 for actual wastewater remediation - Mengyu Di; Wenqi Liu; Dan Shan; Yue Zhao; Changyuan Zhang; Yankun Wang; Ran Yi; Yang Wu; Jing Zheng; Baiqi Wang (Journal of Environmental Management, 2024)

Cost-Effective multifunctional bilayer structural hydrogel evaporator for stable solar desalination and wastewater treatment - Xin-Yu Zhou; Shu-Chao Song; Wen-Xiu Wang; Hui-Ran Jin; Shan Yun; Ai-Bin Huang; Jing Chen (Chemical Engineering Journal, 2024)

NLRP12 inhibits PRRSV-2 replication by promoting GP2a degradation via MARCH8 - Huiyuan Jing; Yuzhen Song; Erzhen Duan; Jie Liu; Wenting Ke; Ran Tao; Yujin Lv; Pandeng Zhao; Wang Dong; Xianghui Li; Yongbin Guo; Huawei Li (Veterinary Microbiology, 2024)

Influence of extreme 2022 heatwave on megacities' anthropogenic CO2 emissions in lower-middle reaches of the Yangtze River - Jingye Tan; Jun Wang; Haikun Wang; Zhu Liu; Ning Zeng; Ran Yan; Xinyu Dou; Xunmei Wang; Meirong Wang; Fei Jiang; Hengmao Wang; Weimin Ju; et al. (Science of The Total Environment, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Optimizing entropy weight model to accurately predict variation of pharmaceuticals and personal care products in the estuaries and coasts of the South China - Yuxin Xie; Jieyi Diao; Jing Meng; Jianwen Wang; Jiaer Zhang; Jingru Zhang; Lulu Zhang; Jonathan Y.S. Leung; Ran Bi; Wenhua Liu; Tieyu Wang (Marine Pollution Bulletin, 2024)

Precise fine-tuning of the defect degree in FeNi-TDC nanoarrays via fluorinated acetic acid for rapid urea-assisted hydrogen production in seawater - Qianqian Wang; Xiaoyan Ma; Fengjin Qu; Ran bi; Senyang Song; Pengcheng Ma; Jing Sun; Fang Chen; Qiufan Tang (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Effect of vegetation on unsaturated soil hydraulic and the slope stability under rainfall - Ji-Peng Wang; Mo-Han Bai; Yi-Ran Tan; Shangqi Ge; Xu-Guang Gao; Abdelali Dadda; Jing-Yi Shen; Jiong Zhang (Rhizosphere, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

Nrf1 Reduces COX-2 Expression and Maintains Cellular Homeostasis After Cerebral Ischemia/Reperfusion By Targeting IL-6/TNF-α Protein Production - Jing Yang; Junqing Yang; Ying Luo; Dongzhi Ran; Rongsong Xia; Qixue Zheng; Peishuang Yao; Hong Wang (Journal of Neuroimmune Pharmacology, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Effects of Dietary Supplementation with Endogenous Probiotics Bacillus subtilis on Growth Performance, Immune Response and Intestinal Histomorphology of Juvenile Rainbow Trout (Oncorhynchus mykiss) - Jing Wang; Dan Fan; Ran Zhao; Tongyan Lu; Shaowu Li; Di Wang (Fishes, 2024)
The rainbow trout (Oncorhynchus mykiss) is an important commercial fish. Studies have shown that probiotics can promote the healthy growth of fish. In this study, we assessed the impact of an endogenous Bacillus subtilis strain (RT-BS07) on the growth, survival and immunological response of juvenile rainbow trout. Additionally, the morphology of rainbow trout’s intestinal tissue was measured. Control (CT) and experimental groups (B) were fed with conventional and probiotic-supplemented diets (1.0 × 108 CFU per gram) for 42 days, respectively. Following feeding, a challenge experiment was carried out with Aeromonas hydrophila at 1.0 × 107 CFU/mL to determine the experimental fish’s tolerance to the bacteria. The results showed that the weight gain rate (WGR) in group B was 118.2%, which was significantly higher than that in group CT (54.86%) after 42 days. The height of intestinal villi and the number of goblet cells increased in group B, thus increasing the resistance of rainbow trout to pathogenic bacteria. The alkaline phosphatase (AKP) activity (U/mg prot) in the liver, spleen and intestinal tissues of group B was significantly higher than that in the CT group. The expression of interleukin-1β (IL-1β) in the intestinal tissue of group B was 6-fold higher than that in group CT. Furthermore, the expression of growth hormone-2 (GH-2) in the spleen was 3-fold higher than that in group CT. After 12 days of A. hydrophila injection, the survival rate was 40% and 70% in group CT and group B, respectively. Collectively, the present study demonstrated that the addition of endogenous B. subtilis strain (1.0 × 108 CFU per gram) to the feed can effectively promote the growth of rainbow trout and enhance immunity, which is beneficial to rainbow trout culture.

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Five new meroterpenes from the seeds of Psoralea corylifolia and their diacylglycerol acyltransferase activity - Xiao-Jing Shao; Meng-Xue Xiu; Xue-Hui Wang; Wen-Hui Xu; Ying-Xiao Xiao; Yuan Gao; Yi-Ran Jiang; Tian-Tian Bei; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2024)

Engineering Phaeodactylum tricornutum exosomes to enhance intracellular fucoxanthin delivery - Fang Tian; Jing Liu; Panpan Wang; Ran Xu; Luyun Cai (Food Bioscience, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Association between long-term ozone exposure and readmission for chronic obstructive pulmonary disease exacerbation - Huajing Yang; Zihui Wang; Yumin Zhou; Zhaosheng Gao; Jing Xu; Shan Xiao; Cuiqiong Dai; Fan Wu; Zhishan Deng; Jieqi Peng; Pixin Ran (Environmental Pollution, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Enhancing the properties of soy protein isolate and dialdehyde starch films for food packaging applications through tannic acid crosslinking - Yuan Zhao; Ran Tian; Qin Zhang; Lianzhou Jiang; Jing Wang; Yan Zhang; Xiaonan Sui (Carbohydrate Polymers, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Ecoregion-wise fractional mapping of tree functional composition in temperate mixed forests with sentinel data: Integrating time-series spectral and radar data - Ziyu Lin; K.H. Cheng; Dedi Yang; Fei Xu; Guangqin Song; Ran Meng; Jing Wang; Xiaolin Zhu; Michael Ng; Jin Wu (Remote Sensing of Environment, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Metabolisms of both inorganic and methyl-mercury in hens reveal eggs as an effective bioindicator for environmental Hg pollution - Zhuhong Wang; Jing Liao; Pengxue Gai; Xiaoling Guo; Wang Zheng; Xue Li; Yulin Ran; Zhongwei Wang; Jiubin Chen (Journal of Hazardous Materials, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Pull-out behavior of the pre-installed lifting anchor with supplementary reinforcement for the precast concrete segments of wind turbine hybrid towers - Wei Ren; Xu-Hong Zhou; Jing-Shen Wang; Yu-Hang Wang; Ji-Ke Tan; Ran Deng; Yao Lu (Engineering Structures, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Evodiamine inhibits growth of vemurafenib drug-resistant melanoma via suppressing IRS4/PI3K/AKT signaling pathway - Xingxian Guo; Shiying Huang; Yonghong Zhang; Hong Wang; Lisha Li; Jianhua Ran; Dilong Chen; Xiaopeng Li; Jing Li (Journal of Natural Medicines, 2024)

Phenethyl isothiocyanate induces cytotoxicity and apoptosis of porcine kidney cells through Mitochondrial ROS-associated ERS pathway - Yuanyuan Zhu; Qiurong Xu; Ruili Zou; Sha Liu; Ran Tao; Shuiping Liu; Xiaowen Li; Lixin Wen; Jing Wu; Ji Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

High fat diet-induced downregulation of TRPV2 mediates hepatic steatosis via p21 signalling - Pengfei Wei; Lixuan Li; Chenqiu Ran; Mingyue Jin; Huijuan Zhao; Kelaier Yang; Yu Wang; Huaqiu He; Mengyang Jia; Hongyan Pan; Qiang Li; Jing Guo (Journal of Physiology and Biochemistry, 2024)

β3 adrenergic receptor activation alleviated PM2.5-induced hepatic lipid deposition in mice - Weijia Gu; Ruiqing Wang; Yanxi Chai; Lu Zhang; Rucheng Chen; Ran Li; Jing Pan; Junyao Zhu; Qinghua Sun; Cuiqing Liu (Science of The Total Environment, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Spatial variation of organic carbon storage and aggregate sizes in the sediment of the Zhangjiang mangrove ecosystem - Ran Yan; Jianxiang Feng; Tao Fu; Qiqi Chen; Zhenyu Wang; Fang Kang; Jing Fang; Guanmin Huang; Qingshu Yang (CATENA, 2024)

Gestational exposure to ambient fine particulate matter disrupts maternal hepatic lipid metabolism - Yunlu Wu; Yirun Wang; Wenhui Zhang; Jing Peng; Li Qin; Lu Zhang; Rucheng Chen; Weijia Gu; Qinghua Sun; Cuiqing Liu; Ran Li (Chemosphere, 2023)

Exploring the potential of magnetic persimmon tannins-based bio-adsorbent for Cd (II) ions removal from water: Experiment and DFT study - Fan Zhou; Lin Gao; Shunyan Cui; Jing Tian; Tong Wang; Guiyin Li; Zhongmin Wang; Chaoke Qin; Dahong Lin; Weijiang Gan; Zhaojin Ran (Journal of Water Process Engineering, 2023)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

Inter-laboratory validation by event-specific qPCR methods for the detection of genetically modified insect and herbicide-tolerant maize DBN9501 - Jing Wang; Bing Xiao; Ruiying Zhang; Haitao Guan; Yang Yang; Yijia Ding; Ran Yuan; Xiaolei Zhang; Lingyan Li; Jingang Liang; Hongtao Wen (Journal of Consumer Protection and Food Safety, 2023)

Medium-chain triglyceride-stabilized docetaxel-loaded HSA nanoparticles effectively inhibited metastatic non-small cell lung cancer - Yunlong Cheng; Xiaoying Pang; Jing Wu; Lingling Zhou; Jinxu Cao; Liuchang Wang; Kang Qian; Peng Yang; Minjun Xu; Dongyu Sheng; Ran Meng; Pengzhen Wang; et al. (Drug Delivery and Translational Research, 2023)

Unprecedented decline in photosynthesis caused by summer 2022 record-breaking compound drought-heatwave over Yangtze River Basin - Jun Wang; Ran Yan; Guoxiong Wu; Yimin Liu; Meirong Wang; Ning Zeng; Fei Jiang; Hengmao Wang; Wei He; Mousong Wu; Weimin Ju; Jing M. Chen (Science Bulletin, 2023)

Bioactive ellagitannins and phenylpropanoid glycosides from the seed of Torreya grandis - Xue-Hui Wang; Xiao-Jing Shao; Yi-Ran Jiang; Tian-Tian Bei; Wen-Hui Xu; Bo-Wen Ren; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2023)

Parametric modeling study for blown-dust secondary pollution and optimal ventilation velocity during tunnel construction - Jinnan Guo; Angui Li; Tianqi Wang; Ran Gao; Dingmeng Wu; Yifei Yin; Jiaxing Li; Jing Hu (Environmental Pollution, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

A mega study of antibiotics contamination in Eastern aquatic ecosystems of China: occurrence, interphase transfer processes, ecotoxicological risks, and source modeling - Abdul Qadeer; Guo Rui; Liu Yaqing; Dai Ran; Chengyou Liu; Dong Jing; Muhammad Anis; Mengyang Liu; Shuhang Wang; Xia Jiang; Xingru Zhao (Journal of Hazardous Materials, 2023)

Complement C3 Enhances LPS-Elicited Neuroinflammation and Neurodegeneration Via the Mac1/NOX2 Pathway - Ran Zhou; Shih-Heng Chen; Zhan Zhao; Dezhen Tu; Sheng Song; Yubao Wang; Qingshan Wang; Jing Feng; Jau-Shyong Hong (Molecular Neurobiology, 2023)
Recent studies showed increased expression of complements in various neurodegenerative diseases, including Alzheimer’s and Parkinson’s diseases. However, the mechanism regulating the expression of complements and their roles in the pathogenesis of neurodegeneration are unclear. We hypothesized that acute neuroinflammation increases the expression and activation of brain complements, which, in turn, participate in chronic neuroinflammation and progressive neurodegeneration. We initially focused on the complement component C3, because C3 can activate microglia by binding to C3 receptors and attaching to damaged neurons destined to be phagocytosed by microglia. We found that complement C3 is upregulated in lipopolysaccharide (LPS)-stimulated neuron/glial cultures. Mechanistic studies revealed that microglia-released proinflammatory factors initiated the enhanced expression of C3 in astroglia during acute neuroinflammation. On the other hand, the sustained C3 expression during chronic neuroinflammation requires releasing damage-associated molecule patterns (DAMPs) from damaged/degenerating brain cells. Our results suggested that DAMPs might act on microglial integrin receptor Mac1 to trigger the activation of NADPH oxidase (NOX2). Activated microglial NOX2 increases the production of extracellular reactive oxygen species (ROS), elevating the levels of intracellular ROS of astroglia and sustaining the astroglial C3 expression. This was supported by the findings showing reduced C3 expression and attenuated neurodegeneration in LPS-treated neuron/glial cultures prepared from mice deficient in Mac1 or NOX2. LPS-induced neurodegeneration and oxidative stress are significantly reduced in C3 KO neuron/glial cultures and mouse brains. Together, this study provides the first evidence demonstrating the role of C3 in regulating chronic neuroinflammation and in driving progressive neurodegeneration.

Effects of whole grain intake on glycemic traits: A systematic review and meta-analysis of randomized controlled trials - Shixiang Li; Aizhen Zong; Ran An; Haiou Wang; Lina Liu; Jie Liu; Xiaofei Guo; Zhixiang Xu; Jing Wang; Duo Li; Fangling Du; Tongcheng Xu (Critical Reviews in Food Science and Nutrition, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Chemical constituents from the aerial parts of Sambucus adnata Wall. and their chemotaxonomic significance - Zheng-Bo Wu; Mei-Mei Zheng; Shu-Ran Qin; Jiang-Li Huang; Dashan Li; Wen-Jing Wang (Biochemical Systematics and Ecology, 2023)

Sustainable utilization of residual grass: effect of anaerobic storage days on chemical composition, fermentation performance, microbial community, and functional profiles of Pennisetum giganteum - Jie Zhao; Zhao-Di Jing; Xue-Jing Yin; Jun-Feng Li; Zhi-Hao Dong; Si-Ran Wang; Tao Shao (Environmental Science and Pollution Research, 2023)

Recognition of microplastics suspended in seawater via refractive index by Mueller matrix polarimetry - Jiajin Li; Hongyuan Liu; Ran Liao; Hongjian Wang; Yan Chen; Jing Xiang; Xiangrong Xu; Hui Ma (Marine Pollution Bulletin, 2023)

PHB2 binds to ERβ to induce the autophagy of porcine ovarian granulosa cells through mTOR phosphorylation - Guangyu Liu; Yifan Wang; Yuxin Zheng; Jing Lv; Yuanyou Li; Ning Liu; Huimin Gao; Haohan Ran; Hong Tang; Zhongliang Jiang (Theriogenology, 2023)

Influence of habitats and physicochemical factors on trophic transfer processes of antibiotics in a freshwater ecosystem: Application of stable isotopes and human health risks - Abdul Qadeer; Zeeshan Ajmal; Liu Hanxia; Dai Ran; Tadiyose Girma Bekele; Kelly L. Kirsten; Sisi Liu; Mengyang Liu; Huang Zhifeng; Dong Jing; Shuhang Wang; Jiang Xia; et al. (Science of The Total Environment, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Sex difference in effects of intermittent heat exposure on hepatic lipid and glucose metabolisms - Guoqing Zhang; Yindan Wang; Ran Li; Jing Peng; Jinna Zhang; Renjie Hu; Lu Zhang; Yunlu Wu; Qinghua Sun; Cuiqing Liu (Science of The Total Environment, 2023)

Impacts of hydraulic conditions on microplastics biofilm development, shear stresses distribution, and microbial community structures in drinking water distribution pipes - Xiao Chen; Xiao-ying Lian; Yi Wang; Sheng Chen; Yi-ran Sun; Guo-lin Tao; Qiao-wen Tan; Jing-chun Feng (Journal of Environmental Management, 2023)

Identifying the geochemical evolution and controlling factors of the shallow groundwater in a high fluoride area, Feng County, China - Shou Wang; Jing Chen; Wei Jiang; Shuxuan Zhang; Ran Jing; Shengyun Yang (Environmental Science and Pollution Research, 2022)

Mechanisms underlying microRNA-222-3p modulation of methamphetamine-induced conditioned place preference in the nucleus accumbens in mice - Qing Shang; Jing Wang; Zhijia Xi; Baoyao Gao; Hongyan Qian; Ran An; Gaojie Shao; Hua Liu; Tao Li; Xinshe Liu (Psychopharmacology, 2022)

Role of jasmonate signaling in rice resistance to the leaf folder Cnaphalocrocis medinalis - Yunqi Zhuang; Xinjue Wang; Lucas Cortés Llorca; Jing Lu; Yonggen Lou; Ran Li (Plant Molecular Biology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Lactate anions participate in T cell cytokine production and function - Jing Wen; Shipeng Cheng; Yaguang Zhang; Ran Wang; Jiefang Xu; Zhiyang Ling; Liyan Ma; Xinghao Ai; Bing Sun (Science China Life Sciences, 2021)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Evaluation and improvement of the greenness of plasma spraying through life cycle assessment and grey relational analysis - Jing Liu; Liming Wang; Fangyi Li; Yanle Li; Xueju Ran; Lin Kong; Yan Fu (The International Journal of Life Cycle Assessment, 2021)

Object-based change detection for VHR remote sensing images based on a Trisiamese-LSTM - Ran Jing; Shuang Liu; Zhaoning Gong; Zhiheng Wang; Hongliang Guan; Atul Gautam; Wenji Zhao (International Journal of Remote Sensing, 2020)

Characterization of phosphorus engineered biochar and its impact on immobilization of Cd and Pb from smelting contaminated soils - Jing Ren; Zixuan Zhao; Amjad Ali; Weidou Guan; Ran Xiao; Jim J. Wang; Sirui Ma; Di Guo; Baoyue Zhou; Zengqiang Zhang; Ronghua Li (Journal of Soils and Sediments, 2020)

Extracting tidal creek features in a heterogeneous background using Sentinel-2 imagery: a case study in the Yellow River Delta, China - Zhaoning Gong; Qiwei Wang; Hongliang Guan; Demin Zhou; Lei Zhang; Ran Jing; Xing Wang; Zhe Li (International Journal of Remote Sensing, 2020)

Benefits of Biochar for Improving Ion Contents, Cell Membrane Permeability, Leaf Water Status and Yield of Rice Under Saline–Sodic Paddy Field Condition - Cheng Ran; Anwari Gulaqa; Jing Zhu; Xiaowei Wang; Siqi Zhang; Yanqiu Geng; Liying Guo; Feng Jin; Xiwen Shao (Journal of Plant Growth Regulation, 2020)

Genome-wide survey and expression analyses of the GRAS gene family in Brassica napus reveals their roles in root development and stress response - Pengcheng Guo; Jing Wen; Jin Yang; Yunzhuo Ke; Mangmang Wang; Mingming Liu; Feng Ran; Yunwen Wu; Pengfeng Li; Jiana Li; Hai Du (Planta, 2019)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Nuclear localization signal in TRIM22 is essential for inhibition of type 2 porcine reproductive and respiratory syndrome virus replication in MARC-145 cells - Huiyuan Jing; Ran Tao; Nan Dong; Sufang Cao; Yanting Sun; Wenting Ke; Yang Li; Jinhe Wang; Yan Zhang; Hui Huang; Wang Dong (Virus Genes, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Performance of yeast-like cell counting (YLCC) using the Sysmex UF-1000i for clinical candiduria screening - He Zhengxin; Zhang Haipu; Cheng Yan; Ran Xiangyang; Chen Jing; Huo Xiaosai; Wang Fukun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Identification and detection sensitivity of Microcystis aeruginosa from mixed and field samples using MALDI-TOF MS - Li-Wei Sun; Wen-Jing Jiang; Jun-Yi Zhang; Wen-Qian Wang; Yang Du; Hiroaki Sato; Masanobu Kawachi; Ran Yu (Environmental Monitoring and Assessment, 2018)

Graphene oxide-coated stir bar sorptive extraction of trace aflatoxins from soy milk followed by high performance liquid chromatography-laser-induced fluorescence detection - Haiyan Ma; Congcong Ran; Mengjiao Li; Jinglin Gao; Xinyu Wang; Lina Zhang; Jing Bian; Junmei Li; Ye Jiang (Food Additives & Contaminants: Part A, 2018)

Cd271 mediates proliferation and differentiation of epidermal stem cells to support cutaneous burn wound healing - Min Zhang; Yongqian Cao; Xiaohong Li; Lizhi Hu; Sahbi Khaled Taieb; Xiaolong Zhu; Jing Zhang; Yongqiang Feng; Ran Zhao; Mingqing Wang; Wenjun Xue; Zhanjie Yang; et al. (Cell and Tissue Research, 2018)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Effect of chemical erosion and freeze–thaw cycling on the physical and mechanical characteristics of granites - Jing Ni; You-Liang Chen; Peng Wang; Su-Ran Wang; Bin Peng; Rafig Azzam (Bulletin of Engineering Geology and the Environment, 2017)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Increased PELP1 expression in rat periodontal ligament tissue in response to estrogens treatment - Jing Wang; Qiang Zhu; Shujun Song; Jun Dong; Lixin Shi; Ran Tao; Yin Ding; Baofa Hong (Journal of Molecular Histology, 2013)

SIRT1 suppresses PMA and ionomycin-induced ICAM-1 expression in endothelial cells - YuYan Jia; Peng Gao; HouZao Chen; YanZhen Wan; Ran Zhang; ZhuQin Zhang; RuiFeng Yang; Xu Wang; Jing Xu; DePei Liu (Science China Life Sciences, 2013)

Bio-immobilization of Cu and Zn in recirculated bioreactor landfill - Yu-Yang Long; Li-Fang Hu; Jing Wang; Cheng-Ran Fang; Ruo He; Dong-Sheng Shen (Environmental Science and Pollution Research, 2010)

Molecular characterization and expression of 1-deoxy-d-xylulose 5-phosphate reductoisomerase (DXR) gene from Salvia miltiorrhiza - Xiangming Yan; Lin Zhang; Jing Wang; Pan Liao; Yan Zhang; Ran Zhang; Guoyin Kai (Acta Physiologiae Plantarum, 2009)

Molecular cloning, characterization and expression analysis of a new gene encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase from Salvia miltiorrhiza - Pan Liao; Wei Zhou; Lin Zhang; Jing Wang; Xiangming Yan; Yan Zhang; Ran Zhang; Li Li; Genyu Zhou; Guoyin Kai (Acta Physiologiae Plantarum, 2009)